Bytes and Backbeats Repurposing Music in the Digital Age - Savage, Steve (University of Michigan Press, 2011)
From Attali's "cold social silence" to Baudrillard's hallucinatory reality, reproduced music has long been the target of critical attack. In Bytes and Backbeats, however, Steve Savage deploys an innovative combination of designed recording projects, ethnographic studies of contemporary music practice, and critical analysis to challenge many of these traditional attitudes about the creation and reception of music. Savage adopts the notion of "repurposing" as central to understanding how every aspect of musical activity, from creation to reception, has been transformed, arguing that the tension within production between a naturalizing "art" and a self-conscious "artifice" reflects and feeds into our evolving notions of creativity, authenticity, and community.